RNA-Seq Analysis in Liver of Selenium-deficient Selenocysteine Lyase Knockout Mouse (P24-023-19). (13th June 2019) - Seale, Lucia; Khadka, Vedbar; Menor, Mark; Sasuclark, Alexandru; Guirguis, Kyrillos; Hashimoto, Ann; Peplowska, Karolina; Tiirikainen, Maarit; Deng, Youping
Abstract: Objectives: Selenium is a trace element critical for appropriate response to oxidative stress in cells. Once ingested, dietary selenium is mostly metabolized by the liver. Selenium is utilized to produce the amino acid selenocysteine, which can be incorporated into selenoproteins, most of them functioning in curbing reactive oxygen species. The enzyme selenocysteine lyase (Scly) decomposes selenocysteine into selenide, and its highest expression and activity occurs in the liver. Disrupting the Scly gene ( Scly − / − ) resulted in overweight mice with hyperlipidemia, hyperinsulinemia and glucose intolerance, phenotype traits that were aggravated by a selenium-deficient diet. In the liver, Scly − / − mice had lower hepatic selenium levels than their wild-type mice counterparts. Our objective was to identify differentially expressed genes and pathways in Scly − /- mice livers affected by dietary selenium levels. Methods: Scly − /- and wild-type mice were fed diets containing 0.08 (mildly low) or 0.25 (adequate) ppm of sodium selenite. We extracted total RNA from livers with a commercial kit. High-quality RNA (RIN ≥ 7) as assessed by a BioAnalyzer was employed in RNA-sequencing. RNA-Seq data analysis was performed on Partek flow software followed by pathway analysis using Ingenuity Pathway Analysis software. Validation of results was pursued by real-time RT-qPCR using specific primer sets. Results: Hepatic RNA-Seq analysis revealed 52 genes differentially regulated by Scly disruption and low dietary selenium levels, encompassing 41 pathways, including PXR/RXR activation, LPS/IL-1-mediated inhibition of RXR function, xenobiotic metabolism signaling, nicotine degradation, adipogenesis, and acyl-CoA hydrolysis. Ten differentially expressed genes were validated by real-time RT-qPCR, including Selenobp2, Eif4ebp3, Mt1, and Mt2. Conclusions: We identified pathways and validated genes in the Scly − /- mouse liver that are implicated in the metabolic phenotype displayed by this model on a low selenium diet. Funding Sources: This project was supported by the National Institutes of Health (NIH) grants U54MD007601 Ola Hawaii (subproject 5544), P30-CA071789–128, R01DK47320, and P20GM103466. The content is solely the responsibility of the authors and does not necessarily represent the official views of the NIH.